Perancangan Model Bisnis Telur Puyuh Steril “Ndok Gemak” Berbasis Sterilisasi Termal Untuk Segmen Rumah Tangga - Perdiyata Kurdi; Dokman Marulitua Situmorang (Jurnal Minfo Polgan, 2026)
The food and culinary sector in Indonesia continues to grow rapidly, but most culinary MSMEs still face challenges in terms of product sustainability, food safety, and market competitiveness. This research aims to design a business model for the sterilized quail egg product "Ndok Gemak" using the Business Model Canvas (BMC) approach, develop effective marketing and distribution strategies, and analyze the business's overall feasibility from market, technical, operational, and financial perspectives. "Ndok Gemak" consists of bacem (sweetened marinated) seasoned quail eggs processed through thermal sterilization at 121°C and 15 psi for 15–20 minutes using airtight retort pouch packaging, resulting in a ready-to-eat product without preservatives and with a shelf life of 1–2 weeks. This business has obtained legal status in the form of a Business Identification Number (NIB) and a Halal Certificate to build consumer trust. The financial feasibility analysis results indicate an estimated revenue of IDR 13,000,000 per month, a net profit of IDR 2,500,000 per month, a break-even point of 500 packs per month, an annual ROI of 333%, and a payback period of four months. The targeted market segments include households, culinary entrepreneurs, and students in the Karanganyar area, with distribution channels through mobile vegetable vendors and social media. However, direct laboratory testing has not yet been conducted and is a priority step before marketing on a larger scale.